Sacred violence in mimetic theory and Levinasian ethics. Issue 4 (2nd October 2019) - Harding, Brian
ABSTRACT: Levinas is famously opposed to the sacred and its association with violence. In Totality and Infinity, he writes that he seeks to describe a relationship with the other that is 'purified of the violence of the sacred.' René Girard's attempt to explain the paradoxical nature of the sacred leads him to a sharp criticism of the sacred and like Levinas, he argued that the sacred is linked to violence and murder. Insofar as they both associate the sacred with violence, Levinas and Girard are often seen as bedfellows. In this paper, I will argue that they are irreconcilable, and that, moreover, reading Levinas with Girard shows just how much sacred violence can still be found in Levinas. It is conceivable that a similar argument could be levied against Girard, but that would be too much for one paper.